Pengaruh Green Marketing Mix Terhadap Green Product Purchase Intention Pada Produk Love Beauty And Planet Di Surabaya - Yuka Nabilah; Dwi Bhakti Iriantini (Equilibrium: Jurnal Ekonomi-Manajemen-Akuntansi, 2022)
This study aims to determine and explain the effect of a green marketing mix on green product purchase intention partially. This study uses a quantitative method with analysis using the application IBM SPSS V.20. the determination of the sample in this study uses purposive sampling techniques which is a non-probability technique where the researcher selects a sample with certain considerations with characteristics that have been determined based on the research objectives, in the hope of answering research problems. The number of samples in this study was 90 respondents. The results of the study are the effect of green product has a significant effect on green product purchase intention, green price has a significant effect on green product purchase intention, the green place has an effect but not significant on green product purchase intention, and green promotion has a significant effect on green product purchase intention.